Temuan Klinis dan Terapi Dini pada Anak dengan Sindrom Ramsay-Hunt - Noerfani, Rahma Rafina; Budianti, Windy Keumala; Permatasari, Nadya Aninditha; Gifani, Fathya Nabila (Jurnal Kedokteran Meditek, 2025)
Introduction: Ramsay-Hunt syndrome is a complication of the varicellazoster virus that causes inflammation of the geniculate ganglion cranialnerve VII. This disease is a rare case in children. This case report aims tohighlight the importance of diagnosis, early examination, andappropriate therapy to prevent complications and poor prognosis. CaseIllustration: A 9 year-old girl presented with clear fluid-filled blisters inher left ear for four days before going to the hospital. Two days after thelesions came out, she complained of her face feeling tilted to the right,difficulty close her left eye, and the corner of her mouth being moredrawn towards the normal side. The left auricular helix fossa regionshowed a rash of multiple vesicles in groups containing clear fluid withan erythematous skin base, distributed unilaterally according to thedermatome. The patient was diagnosed with Ramsay-Hunt syndrome.She was treated with a combination of oral acyclovir andmethylprednisolone injections. Discussion: Antiviral therapy within 24–72 hours after the onset of the rash is very effective for healing of the rashand reducing the duration of pain. Corticosteroid as an antiinflammatory can reduce peripheral nerve damage and edema.Combination of corticosteroid with acyclovir for 7 days in herpes zosteraccompanied by facial paralysis is very effective in significantly reducingacute pain and reducing the risk of complications. Conclusion:The exactdiagnosis and combination of antiviral with corticosteroid therapy inchildren can be beneficial in reducing the duration of lesions and pain aswell as the risk of complications.